2022
DOI: 10.21608/ijmti.2022.172712.1069
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Control of Al-Ce Alloys:‎ A Review

Abstract: The recent research on Al-alloys focuses on the systems that contain intermetallic precipitates with hightemperature stability. Hence using rare earth elements to achieve this purpose minimizes the advantage of conventional casting as one of the most economical fabrication processes, an alternative way becomes mandatory. In this regard, the group of Al-Ce alloys is currently receiving attention as the most suitable high-temperature candidate among the other Al-alloys. These alloys are characterized by their st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It has been reported that this phase is the essential intermetallic phase that controls the high-temperature properties of Al-Ce alloys [11,13]. Several investigations worked on modifying the shape of the secondary Ce-intermetallic phases [12] through either chemical modification [14], rapid solidification [13,15], or applying mechanical/magnetic stirring [16], as well as, most recently, via solidification under ultrasonic vibrations [17]. Among these processes, those related to solidification processing are the most efficient.…”
Section: Microstructure Refinement Of Al-xce Alloysmentioning
confidence: 99%
“…It has been reported that this phase is the essential intermetallic phase that controls the high-temperature properties of Al-Ce alloys [11,13]. Several investigations worked on modifying the shape of the secondary Ce-intermetallic phases [12] through either chemical modification [14], rapid solidification [13,15], or applying mechanical/magnetic stirring [16], as well as, most recently, via solidification under ultrasonic vibrations [17]. Among these processes, those related to solidification processing are the most efficient.…”
Section: Microstructure Refinement Of Al-xce Alloysmentioning
confidence: 99%